1998
DOI: 10.1016/s0896-6273(00)80637-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PS1 Deficiency on Membrane Protein Trafficking in Neurons

Abstract: We have examined the trafficking and metabolism of the beta-amyloid precursor protein (APP), an APP homolog (APLP1), and TrkB in neurons that lack PS1. We report that PS1-deficient neurons fail to secrete Abeta, and that the rate of appearance of soluble APP derivatives in the conditioned medium is increased. Remarkably, carboxyl-terminal fragments (CTFs) derived from APP and APLP1 accumulate in PS1-deficient neurons. Hence, PS1 plays a role in promoting intramembrane cleavage and/or degradation of membrane-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
226
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 347 publications
(257 citation statements)
references
References 42 publications
28
226
2
Order By: Relevance
“…PIP 2 has been shown to play a role in a variety of cell functions, including ion channel modulation, rearrangement of cytoskeleton, and membrane protein trafficking (26). Intriguingly, cellular phenotypes in PIP 2 -compromised cells are reminiscent of those observed in cells expressing FADassociated presenilin mutations, e.g., ion channel and trafficking deficits (15). The potential role of presenilin in PIP 2 metabolism can be further evidenced by occurrence of PS1 in PIP 2 -enriched subcellular compartments, including lipid rafts (44), phagocytic cups (19), lamellipodia (45), and adherent junctions (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PIP 2 has been shown to play a role in a variety of cell functions, including ion channel modulation, rearrangement of cytoskeleton, and membrane protein trafficking (26). Intriguingly, cellular phenotypes in PIP 2 -compromised cells are reminiscent of those observed in cells expressing FADassociated presenilin mutations, e.g., ion channel and trafficking deficits (15). The potential role of presenilin in PIP 2 metabolism can be further evidenced by occurrence of PS1 in PIP 2 -enriched subcellular compartments, including lipid rafts (44), phagocytic cups (19), lamellipodia (45), and adherent junctions (18).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that the presenilins are involved in several additional, ␥-secretase-independent cellular functions including Wnt and Akt signaling (12)(13)(14), membrane protein trafficking (15), ion channel regulation (16,17), and cell junction organization (18). Two of the most consistent cellular changes associated with both PS1 and PS2 FAD-associated mutations include ion channel dysfunction, such as defects in capacitative Ca 2ϩ entry (CCE) (16,17) and membrane trafficking defects, including diminished cell surface delivery of APP (15,(19)(20)(21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It also raises the question as to whether other biochemical impairments or behavioral alterations present in APP V717I transgene mice can be reverted in their double transgenic mice. Regarding that PS1 has pleiotropic roles in brain cell functions, e.g., Notch (Naruse et al, 1998;Song et al, 1999) and N-cadherin (Marambaud et al, 2003) processing, it needs to be answered whether the observed learning deficits of the conditional PS1 knockout mice used in their studies were produced solely by hCTF99, by other PS1-cleaved products, or by the lack of a PS1-dependent physiology.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic mutations in the APP, PSEN1, and PSEN2 genes are responsible for familial early-onset Alzheimer's disease (5,6). PSEN1 and PSEN2 encode polytopic membrane proteins presenilin 1 (PS1) and PS2, respectively, which as components of the ␥-secretase complex play essential role in A␤ production (7,8). Considerable evidence suggests that familial Alzheimer's disease-linked PS1 and PS2 (PS) variants exert their pathogenic influence by selectively elevating the levels of highly fibrillogenic A␤42 peptides (2,4).…”
mentioning
confidence: 99%